PELAKSANAAN PERKAWINAN DAYAK TOBAG DI DESA TERAJU KECAMATAN TOBA KABUPATEN SANGGAU - NIM. A1012211058, RANGGA (Jurnal Fatwa Hukum, 2026)
Abstract The problems addressed in this study focus on how the Dayak Tobag traditional marriage ceremony in Teraju Village is carried out, including the customary stages that contain philosophical values and sacred meanings. The study also highlights the shifts in traditional practices caused by modernization, financial constraints, and social changes within the community. In addition, the research examines the extent to which the implementation of Dayak Tobag traditional marriage aligns with national marriage law and the legal measures taken by the community to ensure protection and legal certainty for married couples. This study employs an empirical legal research method to observe how the Dayak Tobag traditional marriage is practiced in reality. Data were obtained through interviews with customary leaders, village officials, and community members, as well as through direct observation of the customary procession and the collection of relevant documents. The collected data were then analyzed by reducing, presenting, and drawing conclusions so as to provide a clear depiction of the actual implementation of the customary practices and their relationship with national law. Based on the research findings, the Dayak Tobag customary marriage in Teraju Village, Toba District, Sanggau Regency is still carried out through the main customary stages, namely Pado’k, Senggan Bebayo’, Tonya’ Menonya’, Batunang, and the marriage ceremony, which contain sacred meanings and emphasize togetherness, social solidarity, and respect for ancestors. However, there has been a shift (pergeseran) in its practice, as several customary stages have been simplified due to the influence of modernization, financial considerations, and community mobility. Despite this shift, core customary values such as the consent of both spouses, family involvement, and social aspects remain preserved. Moreover, the implementation of the Dayak Tobag customary marriage remains aligned with national marriage law, as reflected in marriage registration as a legal effort to ensure legal protection and certainty regarding the legal status of spouses, children, inheritance rights, and other civil rights and obligations, without diminishing the cultural identity of the Dayak Tobag community. Keywords: Marriage Implementation, Dayak Tobag Custom, Customary Law Abstrak Permasalahan dalam penelitian ini berfokus pada bagaimana pelaksanaan perkawinan adat Dayak Tobag di Desa Teraju dilaksanakan, termasuk tahapan-tahapan adat yang mengandung nilai filosofis dan makna sakral. Penelitian juga menyoroti adanya pergeseran praktik adat akibat pengaruh modernisasi, faktor biaya, dan perubahan sosial di masyarakat. Selain itu, penelitian ini mengkaji sejauh mana pelaksanaan perkawinan adat Dayak Tobag selaras dengan ketentuan hukum nasional serta bagaimana upaya hukum yang ditempuh masyarakat untuk menjamin perlindungan dan kepastian hukum bagi pasangan yang melangsungkan perkawinan. Penelitian ini menggunakan metode penelitian hukum empiris untuk melihat bagaimana perkawinan adat Dayak Tobag dilaksanakan dalam praktik. Data diperoleh melalui wawancara dengan tokoh adat, aparat desa, dan Masyarakat, serta melalui observasi langsung terhadap prosesi adat dan pengumpulan dokumen terkait. Data yang terkumpul kemudian dianalisis dengan cara mereduksi, menyajikan, dan menarik kesimpulan agar memberikan gambaran nyata mengenai pelaksanaan adat dan hubungannya dengan hukum nasional. Berdasarkan hasil penelitian, perkawinan adat Dayak Tobag di Desa Teraju, Kecamatan Toba, Kabupaten Sanggau masih dilaksanakan melalui tahapan adat utama, yaitu Pado’k, Senggan Bebayo’, Tonya’ Menonya’, Batunang, hingga prosesi pernikahan adat, yang mengandung makna sakral serta menekankan nilai kebersamaan, solidaritas sosial, dan penghormatan terhadap leluhur. Namun demikian, terdapat pergeseran dalam praktik pelaksanaannya, di mana beberapa tahapan adat disederhanakan akibat pengaruh modernisasi, pertimbangan biaya, dan mobilitas masyarakat. Meskipun terjadi pergeseran, nilai-nilai inti adat seperti persetujuan kedua mempelai, peran keluarga, dan aspek sosial kemasyarakatan tetap dipertahankan. Selain itu, pelaksanaan perkawinan adat Dayak Tobag tetap selaras dengan hukum perkawinan nasional, yang tercermin dari adanya pencatatan perkawinan sebagai upaya hukum untuk menjamin perlindungan dan kepastian hukum terkait status pasangan, status anak, hak waris, serta hak dan kewajiban keperdataan lainnya, tanpa menghilangkan identitas budaya masyarakat Dayak Tobag. Kata Kunci: Pelaksanaan Perkawinan, Adat Dayak Tobag, Hukum Adat